Windows to Linux migration toolkit - Allen, David (Syngress Pub., 2004)
Linux to Windows Migration Toolkit is a unique book that offers a complete solution for IT managers and sysadmins to migrate from Windows to Linux. It provides migration process planning, automated migration scripts, anti-virus / anti-spam solutions, and specific migration and deployment details for all relevant technologies. The CD includes valuable automated scripts for migrating any flavor of Windows to Linux.